Hypercapnia increases ACE2 expression and pseudo-SARS-CoV-2 entry in bronchial epithelial cells by augmenting cellular cholesterol - Chen, Fei; Matsuda, Aiko; Budinger, G. R. Scott; Sporn, Peter H. S.; Casalino-Matsuda, S. Marina (Frontiers in Immunology, 2023)
Patients with chronic lung disease, obesity, and other co-morbid conditions are at increased risk of severe illness and death when infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Hypercapnia, the elevation of CO2 in blood and tissue, commonly occurs in patients with severe acute and chronic lung disease, including those with pulmonary infections, and is also associated with high mortality risk. We previously reported that hypercapnia increases viral replication and mortality of influenza A virus infection in mice. We have also shown that culture in elevated CO2 upregulates expression of cholesterol synthesis genes in primary human bronchial epithelial cells. Interestingly, factors that increase the cholesterol content of lipid rafts and lipid droplets, platforms for viral entry and assembly, enhance SARS-CoV-2 infection. In the current study, we investigated the effects of hypercapnia on ACE2 expression and entry of SARS-CoV-2 pseudovirus (p-SARS-CoV-2) into airway epithelial cells. We found that hypercapnia increased ACE2 expression and p-SARS-CoV-2 uptake by airway epithelium in mice, and in cultured VERO and human bronchial epithelial cells. Hypercapnia also increased total cellular and lipid raft-associated cholesterol in epithelial cells. Moreover, reducing cholesterol synthesis with inhibitors of sterol regulatory element binding protein 2 (SREBP2) or statins, and depletion of cellular cholesterol, each blocked the hypercapnia-induced increases in ACE2 expression and p-SARS-CoV-2 entry into epithelial cells. Cigarette smoke extract (CSE) also increased ACE2 expression, p-SARS-CoV-2 entry and cholesterol accumulation in epithelial cells, an effect not additive to that of hypercapnia, but also inhibited by statins. These findings reveal a mechanism that may account, in part, for poor clinical outcomes of SARS-CoV-2 infection in patients with advanced lung disease and hypercapnia, and in those who smoke cigarettes. Further, our results suggest the possibility that cholesterol-lowering therapies may be of particular benefit in patients with hypercapnia when exposed to or infected with SARS-CoV-2.